Determination of crack resistance properties of HSLA steel and its welded joint using J-integral - Glavardanov, Ivan; Sedmak, Stojan; Petrovski, Blagoje (Journal of Production Engineering, 1984)
In the present paper an attempt is made to determine crack growth properties of HSLA steel SUMITEN 80P (produced by SUMITOMO-Japan) and its submerged arc welded joint for both elastic and plastic regimes, by single specimen compliance method for J integral evaluation. Single specimen compliance method enables, by unloadings and reloading, the relationship between J and crack extension to be plotted on the basis of only one F-V record.